PENERAPAN MODEL COOPERATIVE LEARNING TIPE TGT (TEAMS GAMES TOURNAMENT) TERHADAP AKTIVITAS BELAJAR SISWA DALAM PEMBELAJARAN SENI MUSIK DI SMP NEGERI 1 PADANG - Lia Nurdiana; Ardipal Ardipal; Yos Sudarman (FBS Universitas Negeri Padang, 2013)
Abstract The research aimend at describing the implementation of cooperative learning model teams games tournament type toward students’ activities in learning music which was better than implementing conventional model at SMP Negeri 1 Padang. Two cllasses werw taken as the sample of the research. VII D was as the control and VII F was as the experiment class. The data was taken from questionnaire given to all sample classes. Before the data was managed, nornality and homogeneity tests were done, followed by descriptive analysis. The result of the research showed that the activities of class used cooperative learning TGT type (Teams Games Tournament) were better than the classused convetional method. Kata kunci : Aktivitas, Pembelajaran, Seni Musik, Model, Cooperative Learning